The impact of war and forced displacement on the mental health of children and adolescents (literature review) - Sokhor Наталія; Yasniy Оксана; Smashna Олена; Hashimova Наталія (Psychosomatic Medicine and General Practice, 2024)
The aim of the research Based on the analysis of scientific sources, to select diagnostic methods for screening predictors of mental disorders in adolescent students under conditions of military stress. Methods Reference databases were searched to select diagnostic methods for screening predictors of mental disorders in adolescent students under military stress. Results The review of the literature proved that military actions are a significant factor of mental traumatization for the entire population of the country. Children and adolescents are the most vulnerable part of the population due to the immaturity of their processes of analytical understanding, emotional regulation, behavioral and motivational patterns, and value and outlook characteristics. A research design was developed to screen predictors of psychological traumatization of adolescents under conditions of military stress. Conclusions Screening of prerequisites for the formation of clinical mental disorders among young people is a predictor of maintaining the nation’s mental health. The study of behavioral patterns, especially aggressiveness, is informative for the prevention of secondary social psychological traumatization among adolescents.